Oral surgery for the general dentist - Dym, Harry; Ogle, Orrett E. (Philadelphia : Saunders, 2012)
This collection of essays by academic and clinical dentists discusses the latest techniques and practices in oral medicine and oral surgical procedure for the general dentistry community.
Preface / Harry Dym and Orrett E. Ogle -- Dedication -- Anxiety control in the dental patient / Orrett E. Ogle and Marc B. Hertz -- Hemostatis in oral surgery / Amandip Kamoh and Jason Swantek -- Oral surgery for patients on anticoagulant therapy : current thoughts on patient management / Ladi Doonquah and Anika D. Mitchell -- Biopsy techniques and diagnoses & treatment of mucocutaneous lesions / Michael H. Chan and Joshua C. Wolf -- Diagnosis and management of common postextraction complications / Joseph E. Pierse, Harry Dym, and Earl Clarkson -- Management of acute postoperative pain after oral surgery / Mark C. Fletcher and Joseph F. Spera -- Risk management in the dental office / Harry Dym -- Endodontic surgery / Suart E. Lieblich -- Local anesthesia : agents, techniques, and complications / Orrett E. Ogle and Ghazal Mahjoubi -- Diagnosis and treatment of temporomandibular disorders / Harry Dym and Howard Israel -- Preoperative evaluation of the surgical patient / Stephen Petranker, Levon Nikoyan, and Orrett E. Ogle -- Pediatric dentoalveolar surgery / Sean W. Digman and Shelly Abramowicz -- Alveolar bone grafting and reconstruction procedures prior to implant placement / Harry Dym, David Huang, and Avichai Stern -- Sinus lift procedures : an overview of current techniques / Avichai Stern and James Green -- Review of antibiotics and indications for prophylaxis / Adam Weiss and Harry Dym -- Exodontia : tips and techniques for better outcomes / Harry Dym and Adam Weiss -- Surgical management of cosmetic mucogingival defects / Harry Dym and Jonathan M. Tagliareni -- Suturing principles for the dentoalveolar surgeon / M. Todd Brandt and W. Scott Jenkins -- Index.
'January 2012.'
Series title on spine: Dental clinics.
Includes bibliographical references and index.
Keywords: Oral Surgical Procedures -- methods; General Practice, Dental -- methods; Surgery, Oral -- methods; Oralchirurgie; Dentistry; Mouth -- Surgery